2009
DOI: 10.1029/2008ja013899
|View full text |Cite
|
Sign up to set email alerts
|

Day‐to‐day variability of the equatorial ionization anomaly and scintillations at dusk observed by GUVI and modeling by SAMI3

Abstract: [1] The day-to-day variability in ionospheric irregularity generation giving rise to equatorial scintillation has remained an unresolved issue over many decades. We take a fresh look at the problem utilizing the global imagery provided by the Global Ultraviolet Imager (GUVI) instrument on NASA's Thermosphere, Ionosphere, Mesosphere Energetics and Dynamics satellite. GUVI has been acquiring images of 135.6-nm emission in the Earth's ionosphere-thermosphere system since 2001. These GUVI disk images at dusk have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 58 publications
6
63
0
Order By: Relevance
“…A similar case was investigated by Zhao et al [2008] for the East Asian region, which suggests that planetary waves modulating the semidiurnal tide might be responsible for the corresponding anomaly enhancement of EIA in the postsunset period. Basu et al [2009] revealed the fact that a counter-electrojet (CEJ) event in the afternoon may contribute to the inhibition of EIA. The cause of the day-today variability of the E × B drift corresponding to the PRE remains unresolved as the information regarding altitude, latitude, longitude, and local time variations of the ion drifts, the neutral winds, and the electric fields are only starting to become available.…”
Section: Discussionmentioning
confidence: 99%
“…A similar case was investigated by Zhao et al [2008] for the East Asian region, which suggests that planetary waves modulating the semidiurnal tide might be responsible for the corresponding anomaly enhancement of EIA in the postsunset period. Basu et al [2009] revealed the fact that a counter-electrojet (CEJ) event in the afternoon may contribute to the inhibition of EIA. The cause of the day-today variability of the E × B drift corresponding to the PRE remains unresolved as the information regarding altitude, latitude, longitude, and local time variations of the ion drifts, the neutral winds, and the electric fields are only starting to become available.…”
Section: Discussionmentioning
confidence: 99%
“…These include airglow observations by the IMAGE (Immel et al 2004(Immel et al , 2007) and TIMED satellites (e.g., Basu et al 2009), and ion drift, density and composition measurements on board the Defense Meteorological Satellite Program (DMSP) (Basu et al 2001;Hartman and Heelis 2007), and Republic of China Satellite (ROCSAT-1) (e.g., Kil et al 2007;Fejer et al 2008a) satellites. In addition, total electric content (TEC) has been obtained from TOPEX satellite data (e.g., Scherliess et al 2008), and magnetic field, plasma density and TEC data have been derived from measurements on board the Challenging Minisatellite Payload (CHAMP) satellite (e.g., Lühr et al 2004).…”
mentioning
confidence: 99%
“…Before the reversal of the drift from upward to downward, there exists an upward drift enhancement named prereversal enhancement (PRE), which is driven by an enhanced eastward electric field lasting about an hour after sunset. At the time of sunset, the F region zonal neutral wind and conductivity gradient caused by the sunset terminator interact to develop an enhanced eastward electric field on the dayside of the terminator and a westward electric field on the nightside (Basu et al, 2009). A clear relation exists between the magnitude of the prereversal enhancement of the vertical plasma drift velocity and the occurrence of post-sunset equatorial spread F (ESF): when a strong prereversal enhancement presents, the irregularities are more likely to develop (Li et al, 2008).…”
Section: Discussionmentioning
confidence: 99%